STRATEGI BISNIS DITENGAH PERSAINGAN KETAT - R Gatot Heru Pranjoto (Eco-Entrepreneur, 2015)
Amidst fierce competition, companies must use the strength of its innovative products (market Driving), which can affect market structure, resources within the company  should be managed  to produce a quality product and efficient, in accordance with the wishes and needs of the market or the consumer, weeks, companies have to do Market research, product design, production and marketing processes. global market requires Approach organization that is used is outside-in, expected the company can immediately transform the desire of markets or customers, and quickly realize these needs so that the market and consumers are expected to quickly accept the offer of the company's products, which is reinforced by selecting the communication channels and creation of two-way communication (marketing Communications), so the market or consumers confident, and choose the company's products.